2016
DOI: 10.1021/acs.jmedchem.5b01503
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of Novel Selenium (Se-NSAID) Molecules as Anticancer Agents

Abstract: The synthesis and anticancer evaluation of novel selenium-nonsteroidal anti-inflammatory drug (Se-NSAID) hybrid molecules are reported. The Se-aspirin analogue 8 was identified as the most effective agent in reducing the viability of different cancer cell lines, particularly colorectal cancer (CRC) cells, was more selective toward cancer cells than normal cells, and was >10 times more potent than 5-FU, the current therapy for CRC. Compound 8 inhibits CRC growth via the inhibition of the cell cycle in G1 and G2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(92 citation statements)
references
References 75 publications
0
91
0
1
Order By: Relevance
“…Previous literature data on the in vitro antitumor effects of NSAID agents, such as acetylsalicylic acid (aspirin), reported their potential to synergistically enhance the cytotoxicity of cisplatin or other chemotherapeutic anticancer agents by different mechanisms, including cell cycle alteration or induction of apoptosis through oxidative stress and mitochondrial dysfunction. 59,[61][62][63] The results of the present study signify that NSAIDs conjugated with ruthenium-arenes represent a promising class of agents with unique in vitro anti-tumor features resulting from the combined properties of both ruthenium-arenes and NSAIDs.…”
Section: Measurement Of Intracellular Reactive Oxygen Speciesmentioning
confidence: 61%
See 1 more Smart Citation
“…Previous literature data on the in vitro antitumor effects of NSAID agents, such as acetylsalicylic acid (aspirin), reported their potential to synergistically enhance the cytotoxicity of cisplatin or other chemotherapeutic anticancer agents by different mechanisms, including cell cycle alteration or induction of apoptosis through oxidative stress and mitochondrial dysfunction. 59,[61][62][63] The results of the present study signify that NSAIDs conjugated with ruthenium-arenes represent a promising class of agents with unique in vitro anti-tumor features resulting from the combined properties of both ruthenium-arenes and NSAIDs.…”
Section: Measurement Of Intracellular Reactive Oxygen Speciesmentioning
confidence: 61%
“…The potential of different metal ions conjugated to NSAIDs to damage DNA and alter the cell cycle was previously demonstrated. [58][59][60] Recent investigation by Kasparkova and colleagues 58 of new Pt(II) conjugates carrying the NSAID diclofenac demonstrated their potential to act as a so-called ''combi-molecule'' which combines the DNA-binding properties of the metal center and antitumor properties of NSAID ligands for cytotoxic activity.…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…[2] Considering the importance of organoselenium compounds in medicinal chemistry, introducing selenium to heterocyclic molecules are expected to find applications in drug discovery programmes. [3] Spirocyclic compounds have attracted great attention in the chemical world because of its original stereostructure and challenging complexity of their synthesis. [4] The spiroindolenines are common structural scaffolds with diverse pharmacological activities and found in various natural products (Figure 1), occupying a prominent position in drug discovery research.…”
mentioning
confidence: 99%
“…Taking into account all these considerations, it is clear that the activity of Se is dependent on the specific constructs in which it is incorporated, and the failure of some Se compounds should not be generalized to all Se derivatives. Recently, our group and many others have demonstrated that the incorporation of Se into organic frameworks, in particular small molecules such as selenocyanate, diselenide, selenourea or selenide, confers unique and very valuable properties against a range of diseases 14,15 , and demonstrate anticancer activity against different cancer types 16,17,18 . Among these small Se-containing mole-cules, Se heterocycles have demonstrated low toxicity for healthy cells, along with promising anticancer effects.…”
Section: Introductionmentioning
confidence: 99%